Finite Element Analysis (FEA) in Electronics Devices and Photonics through Process Oriented Guided Inquiry Learning (POGIL) - Abdul-Kahar, Rosmila; Esa, Fahmiruddin; Gaik Tay, Kim; Hashim, Rathiah; Laham, Mohamad Naqib; Wong, Brian Y.L. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Advance and complex mathematical skill such as finite element analysis are traditionally required to the understanding of electronics devices and photonics applications. Unless the students want to further their studies in theoretical field using complex calculations, students are offered an alternate learning skill such as POGIL by using software simulation packages with embedded FEA to help them visualize the abstract of photonics theories. Students were allowed to modify the original template given in the package, but in the learning process, they have to answer several guided questions in the activity specified. We presented two studies: Thermo Photovoltaic (TPV) cell and Acoustic Levitator (AL), prepared by two groups of third year physics students using COMSOL software and POGIL. As a result, students were able to complete their activities with a new skill of a standard researcher